2018
DOI: 10.1080/10749357.2018.1460946
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dry needling on spasticity, gait and muscle architecture in patients with chronic stroke: A case series study

Abstract: Objectives The objective of this study was to assess the short-term effects of dry needling on spasticity, gait, and muscle architecture of patients with chronic stroke. Methods A case series study was designed; and six chronic stroke patients with ankle spasticity and gait impairment received a single session of dry needling for gastrocnemius medialis, lateralis, and soleus muscles. The main outcome measures were the Modified Modified Ashworth Scale (MMAS), and Timed Up and Go test (TUG). In addition, ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 40 publications
4
32
0
Order By: Relevance
“…Given the novelty of the technique, the optimal frequency of its application is not defined at present. In order not to hinder the daily life of the patients, it was applied once a week in this study based on the minimal time of muscle recuperation 29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the novelty of the technique, the optimal frequency of its application is not defined at present. In order not to hinder the daily life of the patients, it was applied once a week in this study based on the minimal time of muscle recuperation 29) .…”
Section: Discussionmentioning
confidence: 99%
“…As an immediate action, there is rupture of the endomysium and changes in the elongation of actin and myosin fibers. Posteriorly, the inflammatory action allows an improvement in blood flow and oxygen saturation of the stimulated region 28,29) .…”
Section: Introductionmentioning
confidence: 99%
“…9 These have usually been case studies 11,28 or single group studies. 10,29 Although some randomised trials with a comparator 9,27 have been reported, the evidence is still scarce. However, all these studies have been carried out with stroke patients in the chronic phase.…”
Section: Discussionmentioning
confidence: 99%
“…24 Nevertheless, reports are scarce regarding the potential effect of DNT in reducing spasticity in an incomplete SCI (iSCI), 25 and the effect on functionality is not yet described. The hypothesized relation between DNT and decreased spasticity is established in prior research reporting a decrease in noise at the dysfunctional endplate, 26,27 restoration of muscle architecture, 20 contractile properties, 17 and a positive effect on regional brain activity. 19 The MTrPs may be responsible for joint-range restrictions and alterations to muscle activation patterns.…”
Section: Introductionmentioning
confidence: 92%
“…stroke and cerebral palsy) is the dry needling technique (DNT). [17][18][19][20][21][22][23] DNT is a specialized intervention that uses a fine filiform needle to penetrate muscle directly at a myofascial trigger point (MTrP). 24 Nevertheless, reports are scarce regarding the potential effect of DNT in reducing spasticity in an incomplete SCI (iSCI), 25 and the effect on functionality is not yet described.…”
Section: Introductionmentioning
confidence: 99%